A Feasibility Analysis of the Use of IEEE 802.11ah to extend 4G Network Coverage - Rini Cahyani; Doan Perdana; Ahmad Tri Hanuranto (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2020)
The 4G LTE network has been launched in many countries including Indonesia, and all telecommunications operators are competing to expand their service coverage. Due to various reasons, there are a lot of areas that remains uncovered by the 4G LTE network. With the increase in cellular traffic, operators must continue to improve their service coverage. One of the scenarios to expand the service coverage is by offloading the traffic to a more cost-effective 802.11ah network in which one 802.11ah access point can serve thousands of mobile devices and support the Machine-to-Machine (M2M)/Internet of Things (IoT) communication. This study simulates the effect of the number of nodes on MCS performance evaluation of the 802.11ah protocol. The simulation is conducted by utilizing NS3 software to evaluate the throughput, delay, packet delivery ratio and energy consumption. This study also simulates 802.11ah coverage prediction to expand the LTE networks by utilizing Atoll Radio Planning Software. The results show that the performance obtained by varying the number of nodes/users from 100 to 1000 nodes is technically acceptable. In addition, the service coverage of 802.11ah network can solve the problem of blank spot area.